”Vem skall befria mig från detta förskräckliga förflutna?”: Om patientperspektiv, historia och metod - Vallström, Maria (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
In this article I discuss how to deal with a strong biased material, from an asylum, in an effort to gain new knowledge by setting the scene with the patient in the middle. In this re-reading of historical records, I especially focus on the use of the foucauldian perspective as a help in “cutting” in the material, and consequences of my choice to follow the patient, not the asylum or the time period, primarily. That choise makes it necessary to consider contextualization on different levels. Finally, interpretation and subjectivation is discussed as a complex matter involving many voices, using an example from Salberga hospital in Sweden, an asylum opening in 1930, intedended for “asocial, imbecile men”.